Education Scenario, Formulation and Implementation for Development to the Slow Learners of the Tribes of TTAADC (Tripura Tribal Areas Autonomous District Council): Exploring the Impact of Education on Slow Learners in TTAADC (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Education is the parts and parcel in every steps of human life. It likes the backbone of a man. Most of the people in the world do not know its quality and power. Those who accepted to this beautiful gift are to be known the world. The blamers and unwanted persons to this education will suffer in every moment to survive in his life.